Evolving epidemiology of carbapenemase-producing Enterobacterales: one hospital's infection prevention and control response over nine years. (June 2021) - Foley, M.; Duffy, F.; Skally, M.; McCormack, F.; Finn, C.; O'Connor, M.; Cafferkey, J.; Thomas, T.; Burns, K.; Fitzpatrick, F.; O'Connell, K.; Smyth, E.G.; et al.
Summary: Background: Preventing carbapenemase-producing Enterobacterales (CPE) transmission is a significant challenge for hospital infection prevention and control teams (IPCTs). Control measures include screening at-risk patients, contact tracing, and the isolation of carriers with contact precautions. Aim: The evolution of infection prevention and control measures was assessed in a tertiary acute care hospital with predominately multi-bedded patient accommodation, from 2011 to 2019 as cases of CPE increased. The implications for, and the response and actions of, the IPCT were also reviewed. Methods: CPE data collected prospectively from our laboratory, IPCT, and outbreak meeting records were reviewed to assess how the IPCT adapted to the changing epidemiology, from sporadic cases, to outbreaks and to localized endemic CPE. Findings: Of 178 cases, 152 (85%) were healthcare-associated and there was a marked increase in cases from 2017. The number of screening samples tested annually increased from 1190 in 2011 to 16, 837 in 2019, and six outbreaks were documented, with larger outbreaks identified in later years. OXA-48 carbapenemase was detected in 88% of isolates and attendance at outbreak meetings alone accounted for 463.5 h of IPCT members, and related staff time. Conclusion: Despite considerable efforts and time invested by the IPCT, the number of CPE cases is increasing year-on-year, with more outbreaks being reported in later years, albeit partly in response to increased screening requirements. Infrastructural deficits, the changing epidemiology of CPE, and national policy are major factors in the increasing number of cases.